Influence of Behavioral Counseling Techniques, Token Economy and Parent’s Parenting Class of Behaviour Prosocial X Syamsulhude Tegallinggah - Fuadi, Luthfi (International Journal of Psychosocial Rehabilitation, 2017)
Research this aims to determine: (1) differences in prosocial behavior among students who received behavioral counseling techniques token economy with students who do not receive behavioral counseling techniques token economy,(2) differences in prosocial behavior among students who are parenting her acceptance to students who are parenting of his rejection parents, and (3) the effect of the interaction of behavioral counseling techniques token economy and parenting parents toward prosocial behavior. This research is a quasi-experimental design with nonequivalent pretest-posstest control.group design. The population of this research is the class x totaling 30 students. Samples were taken by using purposive sampling with the number of members of the sample 14 students who have low prosocial behavior and very low. Data collection methods used were a questionnaire and analyzed by analysis of variance of two lanes. Research results revealed that: (1) there are differences in prosocial behavior of students who received behavioral counseling techniques token economy and students do not get, (2) there are no differences in prosocial behavior among students who are parenting their parents acceptance and students who are parenting their parents rejection and(3) there is no interaction effect behavioral counseling techniques token economy and parenting parents toward prosocial behavior. The results of this research can be used as a reference for teachers to be able to support Counseling in providing guidance to students who do not understand prosocial behavior.